A native heritage : images of the Indian in English-Canadian literature - Monkman, Leslie (Heritage, 1981)
This survey of English-Canadian literature is the first comprehensive examination of white writers turning to the Indian and his culture for standards and models by which they can measure their own values and goals; for patterns of cultural destruction, transformation, and survival; and for sources of native heroes and indigenous myths.